Bifurcation for a free-boundary tumor model with angiogenesis. (June 2017) - Huang, Yaodan; Zhang, Zhengce; Hu, Bei
Abstract: We consider a free boundary tumor model with vasculature which supply nutrients to the tumor, so that ∂ σ ∂ n + β ( σ − σ ¯ ) = 0 holds on the boundary, where a positive constant β is the rate of nutrient supply to the tumor and σ ¯ is the nutrient concentration outside the tumor. The tumor cells proliferate at a rate μ . We show that for each μ 2, μ 4, μ 6, μ 8, ⋯, symmetry-breaking stationary solutions bifurcate from the radially symmetric stationary solutions.